The Impact of the Independent Learning Independent Campus (MBKM) Internship Program on Students' Soft Skills, Hard Skills and Work Readiness: Impact Analysis on Mulawarman University Students - Chandra, Putri Ayu Tanti; Anwar, Khairil (Dinasti Publisher, 2025)
This study aims to examine the impact of the Independent Learning Campus Independent Internship Program (MBKM) on the development of Soft Skills, Hard Skills, and Work Readiness of Mulawarman University students. The main focus of the study is how students improve their work readiness by improving soft skills and hard skills after undergoing the MBKM program. The results of the study prove that Soft Skills (X1) and Hard Skills (X2) have a significant impact on Work Readiness (Y) simultaneously. Students who experience an increase in soft skills and hard skills after undergoing the MBKM program feel more ready to enter the workforce. This finding shows that work readiness can be achieved by developing effective soft skills and improving relevant hard skills. The study also revealed that soft skills such as communication skills, inter-member cooperation, and in handling problems have a crucial role in increasing the level of student readiness to work. Meanwhile, improving hard skills, including technical and intellectual abilities, also plays a significant role in supporting work readiness. Although there is an increase in work readiness with the MBKM program, there are challenges in optimal implementation, especially related to the application of soft skills and hard skills in real work situations. Therefore, a comprehensive and sustainable strategy is needed to continuously improve students' work readiness by developing soft skills and hard skills continuously. Overall, the MBKM program has proven effective in facilitating efforts to develop students' soft skills and hard skills, thereby increasing their readiness to work. This program makes a significant contribution in creating graduates who are ready to face challenges in the professional world and can adapt to their work scope which tends to change and compete with each other.